Exploring the sustained impact of the Mindfulness-Based Stress Reduction program: a thematic analysis - Yavuz Sercekman, Meltem (Frontiers in Psychology, 2024)
This study aimed to explore the time-varying impact of the Mindfulness-Based Stress Reduction (MBSR) program, specifically examining its effects on various variables three months, one year, and three years after program completion. Additionally, the study aimed to identify the barriers and facilitators in maintaining mindfulness practice over time and the preferred mindfulness practices among participants in three distinct time groups. The study utilized a qualitative research design, conducting semi-structured interviews with 45 participants who had completed the 8-week MBSR program at different time points. Thematic analysis was employed to analyze the qualitative data obtained from the interviews, allowing for the identification of key themes and patterns. The findings revealed that the effectiveness of the MBSR program varied at different times and across different variables. Immediately after completing the program, participants experienced a significant decrease in stress levels and an increase in awareness. One year later, the program continued to have positive effects on inner calm, coping mechanisms, and relationships. Three years after completing the program, its long-term impact was observed in the adoption of a mindful lifestyle, increased compassion and kindness, and ongoing personal growth. The study highlights the transformative potential of the MBSR program beyond short-term symptom relief. The long-term effects observed in overall well-being emphasize the sustained efficacy of mindfulness-based interventions. The identified barriers and facilitators in maintaining mindfulness practice provide insights for program implementation and individual engagement. By understanding the long-term impact and preferences of participants, tailored interventions can be developed to maximize the benefits of the MBSR program for individuals over time.